Factors associated with inmate escapes from correctional institutions. - Sturrock, Robert C. (University of Ottawa (Canada), 1993)
The objective of this study is to examine the factors which might be related to escapes from correctional institutions. Static and dynamic/situational factors were analyzed. Data were collected on escapees and non-escapees. The escapee sample consisted of 35 inmates who had escaped from federal (medium and maximum security) correctional institutions between 1990-04-01 and 1992-03-31. The escapee sample was compared to a random sample of inmates (N = 35) who did not escape during the same period, so that static variables which might differentiate the two groups could be identified. Analyses of the results of static factors showed that significant differences were found between escapee and non-escapee groups. Escapees were more frequently found to have had a history of the following: property offences as the major offence, parole revocation, escape, federal term, drug/alcohol abuse, and institutional misconduct. Escapees were serving significantly longer sentences, were younger, and had more previous criminal convictions. They served an average length of sentence of 5.7 years prior to escape. Among some cases in which escapees and/or staff did identify the factors precipitating the escapes, the following factors were noted: family problems, parole problems, problems with other inmates, outstanding criminal charges, or institutional administrative problems. Moreover, approximately one-quarter of all escapees were under the influence at the time of escape. Slightly over one-quarter had recent parole revocations. Almost one-third had received recent transfers prior to escape. The majority of escapes were planned. Approximately three-quarters of the escapees fled with 1 or more other inmates. Most of the escapees absconded during the evening hours. Findings from this study showed that both static and dynamic/situational factors should be taken into account when explaining escape behaviour. Escape behaviour can be best explained by a combination of prisonization theory, rational choice theory, moral self-transcendence, and the cognitive model. (Abstract shortened by UMI.)
Keywords: Sociology, Criminology and Penology.